2020
DOI: 10.1039/d0cc00886a
|View full text |Cite
|
Sign up to set email alerts
|

DME carbonylation over a HSUZ-4 zeolite

Abstract: Molecule diffusion through the abundant 8-MR pore openings on the side surfaces of a HSUZ-4 rod facilitated DME carbonylation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 43 publications
2
30
0
Order By: Relevance
“…At Si : Al > 39 with the most stable skeleton as the structure, by choosing the desorption temperature larger than 850 K (strong Brønsted acid site), we found that 24 zeolites hit the target. Among them, 11 zeolites (ATT, BIK, EON, GOO, JBW, MAZ, MON, MOR, SZR, THO and WEN) were already synthesized in the form of aluminosilicate with high Si : Al ratio (Si : Al > 5) where 4 of them (BIK, 98 MAZ, 99 MOR 93 and SZR 100 ) have indeed been reported to have strong Brønsted acid sites.…”
Section: Advanced Zeolite Applications Using ML Potentialsmentioning
confidence: 99%
“…At Si : Al > 39 with the most stable skeleton as the structure, by choosing the desorption temperature larger than 850 K (strong Brønsted acid site), we found that 24 zeolites hit the target. Among them, 11 zeolites (ATT, BIK, EON, GOO, JBW, MAZ, MON, MOR, SZR, THO and WEN) were already synthesized in the form of aluminosilicate with high Si : Al ratio (Si : Al > 5) where 4 of them (BIK, 98 MAZ, 99 MOR 93 and SZR 100 ) have indeed been reported to have strong Brønsted acid sites.…”
Section: Advanced Zeolite Applications Using ML Potentialsmentioning
confidence: 99%
“…No existence of a larger channel system leads to a low mass-transfer efficiency for EU-12, and this is the reason why this catalyst shows a low DME conversion (<24%) even at a higher reaction temperature of 240 °C. Shen et al 20 In 2005, a high-silica zeolite Ruhr University Bochum-fortyone (RUB-41) with a 2D pore system of intersecting 8-MR (5.0 × 2.7 Å) and distorted 10-MR (6.5 × 4.0 Å) channels, framework type code RRO, was synthesized by Gies et al 22 via calcination of another layered silicate RUB-39. During the calcination process, the 2D pore system of RUB-41 was situated in the interlayer space through topotactic condensation of RUB-39.…”
Section: Introductionmentioning
confidence: 99%
“…No existence of a larger channel system leads to a low mass-transfer efficiency for EU-12, and this is the reason why this catalyst shows a low DME conversion (<24%) even at a higher reaction temperature of 240 °C. Shen et al reported that SUZ-4 zeolite can give comparable DME conversion and stability to ZSM-35 in the DME carbonylation reaction. Most recently, SSZ-13 zeolite, as uncovered by Davis et al, realized catalyzing DME carbonylation at a much lower temperature of 165 °C.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, catalysts for this process are mainly divided into two types: zeolite catalysts (such as mordenite (MOR) [5], ZSM-35 [6], ZSM-5 [7], and HFER [8,9]) and heteropoly acid catalysts [10,11]. In recent years, EU-12 [12], SSZ-13 [13], and HSUZ-4 [14] zeolites have also been used in this reaction. However, owing to its unique structure and properties, MOR occupies an important position in the DME carbonylation reaction.…”
Section: Introductionmentioning
confidence: 99%